Critical selling : - Kane, Nick (John Wiley & Sons, Inc., 2016)
This book details the winning strategies and skills that have supercharged the sales force of program alumni like OptumHealth, Santander Bank, Daimler Trucks, California Casualty, and many more. Concrete, actionable steps show you how to plan a productive sales call, identify customer needs, differentiate yourself from the competition, and wrap up the sale. You'll also learn proven techniques for building rapport, overcoming objections, dealing with price pressures, and handling the million little things that can derail an otherwise positive sales interaction.